2019
DOI: 10.1016/j.bpj.2018.11.3127
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Membrane Curvature and Cholesterol: Role of Palmitoylated Caveolin-1

Abstract: Caveolin-1 (cav-1) is an important player in cell signaling and endocytosis that has been shown to colocalize with cholesterol-rich membrane domains. Experimental studies with varying cav-1 constructs have suggested that it can induce both cholesterol clustering and membrane curvature. Here, we probe the molecular origin of membrane curvature and cholesterol clustering by cav-1 by using coarse-grain molecular dynamics simulations. We have performed a series of simulations of a functionally important cav-1 cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 98 publications
(146 reference statements)
4
59
0
Order By: Relevance
“…Regarding molecular dynamic simulation studies directly related to caveolae, it has been reported that caveolin-1 can induce CHOL clustering not only in the inner membrane leaflet but also in the opposing leaflet, even when using symmetric bilayers of PC 16:0/16:0 in the absence or presence of 30% CHOL [46]. A positive membrane curvature was observed upon caveolin-1 binding to the CHOL-containing bilayers.…”
Section: Lipid Interdigitation and Simulation Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding molecular dynamic simulation studies directly related to caveolae, it has been reported that caveolin-1 can induce CHOL clustering not only in the inner membrane leaflet but also in the opposing leaflet, even when using symmetric bilayers of PC 16:0/16:0 in the absence or presence of 30% CHOL [46]. A positive membrane curvature was observed upon caveolin-1 binding to the CHOL-containing bilayers.…”
Section: Lipid Interdigitation and Simulation Studiesmentioning
confidence: 99%
“…There is evidence that caveolin may function as a scaffolding protein to stabilize rafts in such domains at the PM as it has been reported to reduce uptake of membrane associated molecules (for reviews, see [72,73]). There is still much to learn about interactions between these proteins and membrane lipids, but since cavin can bind to PS [61], caveolin can interact with CHOL and sphingolipids [46,71,74], PS can interact with CHOL [10,53], and cavin interacts with caveolin [75,76], it is clear that these proteins and lipids can form a network of importance for formation of caveolae.…”
Section: Caveolaementioning
confidence: 99%
“…Caveolae emerge from the interaction of caveolin, a membrane-spanning hairpin-like protein, with cholesterol in lipid-raft microdomains. Upon binding to lipid bilayers, caveolin promotes cholesterol clustering and is able to form higher-order hetero-oligomeric complexes that induce the positive membrane curvature and yield vesicular structures of 50 to 80 nm in diameter [ 47 , 48 , 49 ]. However, unlike the ubiquitous CCPs, dramatic differences have been observed for caveolar densities within different cell types and tissues [ 50 ] and, therefore, their contribution to endocytic dynamics varies widely.…”
Section: Enhancing Ion Internalizationmentioning
confidence: 99%
“…One such protein is ABCA1 protein that maintains intracellular cholesterol levels [98,99], which signals the overexpression of P-glycoprotein (P-gp) leading to multidrug resistance (MDR) in cancer cells [99][100][101]. Caveolin-1 also contributes to MDR [102] possibly by transporting cholesterol to the plasma membrane through various mechanisms [103,104]. This therefore further strengthens the hypothesis that depriving cells of the cholesterol and lipids may prove to be a viable strategy to disrupt the complex interactions of cancer-related pathways, thus forcing cancer cells to die.…”
Section: Cellular Control Of Cholesterol Homeostasismentioning
confidence: 99%